The statements that are true about this step are:
A mobile application, sometimes known as an app, is a computer program or software application that is meant to operate on a mobile device, such as a phone, tablet, or watch.
An app is a software program that allows users to do certain functions on their mobile or desktop device. Apps are either pre-installed on your device or downloaded through a specialized app store, such as the Apple App Store. Apps are usually created in a variety of programming languages.
Learn more about Apps:
brainly.com/question/11070666
#SPJ1
Answer: Forest root domain is used in the Active Directory forest for the first domain section.A domain is defined as the cluster of databases. This domains has Schema Admin groups and Admin of enterprise.
Forest is defined as the boundaries inside which the accessing of the network can be done by the clients. Root is the section that is at the highest level in the complete domain name system.The combination of these two section form the forest root domain system.
Answer:
The formula in Excel is:
=($B$6 - $B$5 - $B$7)* $B$8
Explanation:
Required
Use of absolute reference
To reference a cell using absolute reference, we have to include that $ sign. i.e. cell B5 will be written as: $B$5; B6 as $B$6; B7 as $B$7; and B8 as $B$8;
Having explained that, the formula in cell B13 is:
=($B$6 - $B$5 - $B$7)* $B$8
Answer:
Software as a Service (SaaS)
Explanation:
Cloud computing can be defined as a type of computing that requires shared computing resources such as cloud storage (data storage), servers, computer power, and software over the internet rather than local servers and hard drives.
Generally, cloud computing offers individuals and businesses a fast, effective and efficient way of providing services.
Cloud computing comprises of three (3) service models and these are;
1. Platform as a Service (PaaS).
2. Infrastructure as a Service (IaaS).
3. Software as a Service (SaaS).
Software as a Service (SaaS) can be defined as a cloud computing delivery model which involves the process of making licensed softwares available over the internet for end users on a subscription basis through a third-party or by centrally hosting it.
Hence, Software as a Service (SaaS) is an example of a cloud computing environment that provides users with a web based email service. Therefore, if you pay a subscription fee to use an application via the internet rather than purchasing the software outright, the app is called a Software as a Service (SaaS) application.
Some examples of SaaS applications are Salesforce, Google apps, Bigcommerce, Dropbox, Slack etc.
Answer:
C
Explanation:
Answer: the answer is 1
Explanation:
edge 2021
∃x (P(x) ∧ D(x))
Negation: ¬∃x (P(x) ∧ D(x))
Applying De Morgan's law: ∀x (¬P(x) ∨ ¬D(x))
English: Every patient was either not given the placebo or not given the medication (or both).
(a) Every patient was given the medication.
(b) Every patient was given the medication or the placebo or both.
(c) There is a patient who took the medication and had migraines.
(d) Every patient who took the placebo had migraines. (Hint: you will need to apply the conditional identity, p → q ≡ ¬p ∨ q.)
Answer:
P(x): x was given the placebo
D(x): x was given the medication
M(x): x had migraines
Explanation:
(a) Every patient was given the medication
Solution:
∀x D(x)
∀ represents for all and here it represents Every patient. D(x) represents x was given the medication.
Negation:¬∀x D(x).
This is the negation of Every patient was given the medication.
The basic formula for De- Morgan's Law in predicate logic is:
¬(P∨Q)⇔(¬P∧¬Q)
¬(P∧Q)⇔(¬P∨¬Q)
Applying De Morgan's Law:
∃x ¬D(x)
∃ represents there exists some. As D(x) represents x was given the medication so negation of D(x) which is ¬D(x) shows x was not given medication. So there exists some patient who was not given the medication.
Logical expression back into English:
There was a patient who was not given the medication.
(b) Every patient was given the medication or the placebo or both.
Solution:
∀x (D(x) ∨ P(x))
∀ represents for all and here it represents Every patient. D(x) represents x was given the medication. P(x) represents x was given the placebo. V represents Or which shows that every patient was given medication or placebo or both.
Negation: ¬∀x (D(x) ∨ P(x))
This is the negation or false statement of Every patient was given the medication or the placebo or both.
Applying De Morgan's Law:
∃x (¬D(x) ∧ ¬P(x))
∃ represents there exists some. As D(x) represents x was given the medication so negation of D(x) which is ¬D(x) shows x was not given medication. As P(x) represents x was given the placebo so negation of P(x) which is ¬P(x) shows x was not given placebo. So there exists some patient who was neither given medication nor placebo.
Logical expression back into English:
There was a patient who was neither given the medication nor the placebo.
(c) There is a patient who took the medication and had migraines.
Solution:
∃x (D(x) ∧ M(x))
∃ represents there exists some. D(x) represents x was given the medication. M(x) represents x had migraines. ∧ represents and which means patient took medication AND had migraines. So the above logical expression means there exists a patient who took medication and had migraines..
Negation:
¬∃x (D(x) ∧ M(x))
This is the negation or false part of the above logical expression: There is a patient who took the medication and had migraines.
Applying De Morgan's Laws:
∀x (¬D(x) ∨ ¬M(x))
∀ represents for all. As D(x) represents x was given the medication so negation of D(x) which is ¬D(x) shows x was not given medication. As M(x) represents x had migraines so negation of ¬M(x) shows x did not have migraines. ∨ represents that patient was not given medication or had migraines or both.
Logical expression back into English:
Every patient was not given the medication or did not have migraines or both.
(d) Every patient who took the placebo had migraines.
Solution:
∀x (P(x) → M(x))
∀ means for all. P(x) represents x was given the placebo. M(x) represents x had migraines. So the above logical expressions represents that every patient who took the placebo had migraines.
Here we are using conditional identity which is defined as follows:
Conditional identity, p → q ≡ ¬p ∨ q.
Negation:
¬∀x (P(x) → M(x))
¬∀ means not all. P(x) implies M(x). The above expression is the negation of Every patient who took the placebo had migraines. So this negation means that Not every patient who took placebo had migraines.
Applying De Morgan's Law:
∃x (P(x) ∧ ¬M(x))
∃ represents there exists some. P(x) represents x was given the placebo. ¬M(x) represents x did not have migraines. So there exists a patient who was given placebo and that patient did not have migraine.
Logical expression back into English:
There is a patient who was given the placebo and did not have migraines.